2007
DOI: 10.1002/ajmg.a.31551
|View full text |Cite
|
Sign up to set email alerts
|

Increased rate of major birth malformations in infants with neonatal “asymmetric crying face”: A hospital‐based cohort study

Abstract: Asymmetric crying face (ACF) is a minor anomaly found in 3-8 per 1,000 births, which may be associated with other anomalies. Previous studies on this topic included small groups of selected subjects, resulting in large variations in findings. The aim of this study was to examine the characteristics and associated anomalies of newborn infants with ACF compared with the general population of newborn infants. The study included newborn infants delivered between 1993 and 2003 at the Department of Neonatology of Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…(6) Hemihypertrophy, (14) collodion baby, (15) cystic lymphangioma, (16) and pulmonary agenesis (17) also have been reported in association with ACF.…”
Section: Associated Malformations and Syndromesmentioning
confidence: 92%
See 2 more Smart Citations
“…(6) Hemihypertrophy, (14) collodion baby, (15) cystic lymphangioma, (16) and pulmonary agenesis (17) also have been reported in association with ACF.…”
Section: Associated Malformations and Syndromesmentioning
confidence: 92%
“…The reported frequency of major malformations in retrospective studies is high (range, 5% to 70%) but in prospective studies is approximately 10% (range, 5% to 20%), probably because of less selection bias. (5) Dubnov-Raz and associates (6) found that major malformations occurred in 7% of infants who had ACF, while minor anomalies were noted in 15% and deformations in 4.6%. The risk of associated major malformations with ACF is 3.5-fold higher compared with that in the general population.…”
Section: Associated Malformations and Syndromesmentioning
confidence: 96%
See 1 more Smart Citation
“…Familial transmission, mostly sporadic, has also been reported in a few cases. Incidence of it is between 0.3 and 0.6% [5]. Pathogenesis of hypoplasia of congenital unilateral depressor anguli oris has not been known yet.…”
Section: Discussionmentioning
confidence: 98%
“…A number of other congenital disorders exhibit a similar unilateral, left-sided, and female predominance. These include congenital ptosis, with or without Marcus-Gunn jaw-winking aberrant innervations, 55,56 and congenital facial palsy, 57 among others. The cranial nerves involved are all vascularized in their peripheral portions by the ipsilateral internal carotid artery, which points to a similar embolic causal mechanism.…”
Section: Other Cranial Nerves and Misinnervation Syndromesmentioning
confidence: 99%